1888 Terr. of Mont. Comp. Stat. 513. - (:unkn) unknown (My University, 1888)
Ch. 4, § 66: It shall be unlawful for any person within the limits of any city, town or village in this territory, to bear concealed upon his person any dirk, dagger, pistol, revolver, or other deadly weapon.
Keywords: CARRY - CONCEALED